2019
DOI: 10.3389/fnbeh.2019.00102
|View full text |Cite
|
Sign up to set email alerts
|

Neuroticism Modulates the Functional Connectivity From Amygdala to Frontal Networks in Females When Avoiding Emotional Negative Pictures

Abstract: Amygdala activity was previously found to correlate with neuroticism as an effect of valence, but so far few studies have focused on motivational context. The network subserving altered amygdala activity has not yet been investigated although some studies showed strong effective connections with prefrontal cortex (PFC). The goal of this study was to test the modulatory role of neuroticism on the functional connectivity (FC) between amygdala and other brain regions, especially PFC, during emotion processing fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 61 publications
0
7
0
Order By: Relevance
“…Previous literature has suggested that neuroticism is associated with altered functional connectivity in amygdalarelated circuits, [56][57][58] and that low levels of endocannabinoids in this circuit increase proneness to anxiety and negative emotions. 42 Our failure to find a relationship with selfreported trait neuroticism may be an issue of power, particularly when considering that sex, age and factors affecting state anxiety may also modulate the effect.…”
Section: Discussionmentioning
confidence: 99%
“…Previous literature has suggested that neuroticism is associated with altered functional connectivity in amygdalarelated circuits, [56][57][58] and that low levels of endocannabinoids in this circuit increase proneness to anxiety and negative emotions. 42 Our failure to find a relationship with selfreported trait neuroticism may be an issue of power, particularly when considering that sex, age and factors affecting state anxiety may also modulate the effect.…”
Section: Discussionmentioning
confidence: 99%
“…Neuroimaging studies had suggested the involvement of amygdala (as part of the limbic system) in attention process. 23,24 Thus, it can be predicted that prefrontal cortical top-down control contributes to the inhibition of responses generated by limbic functioning, 25 which might include emotional responses in which individuals with neurotic personality would appraise the challenge as more stressful and display more negative effect following the experience. Therefore, individual differences in association to limbic system can influence the cognitive process due to stress responses in reaction to stimuli and consequently increase in intensity and high concentration of attention.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, individual differences in association to limbic system can influence the cognitive process due to stress responses in reaction to stimuli and consequently increase in intensity and high concentration of attention. 24,26 as well as implication on emotional process. 27 However, the finding of the current study should be taken with caution due to the small sample size and the enlightment of cognitive flexibility from the single measure of P300 component without looking at other components.…”
Section: Discussionmentioning
confidence: 99%
“…Neuroticism is a partially stable trait, characterized by negative affect and increased sensitivity to stress. Neuroimaging studies suggest that neuroticism is associated with impaired functional connectivity of the amygdala with regulatory cortical networks [28]. In large samples, neuroticism was highly correlated with depression in younger and older adults and both the conditions had a substantially overlapping genetic contribution [29].…”
Section: Discussionmentioning
confidence: 99%